From Curative to Preventive: Operationalising Hospital Without Walls for More Efficient Indonesia’s Public Health Service Transformation in 2045 - Amanda, Qorry; Akmal, Muhammad Fikri; Kusumawati, Fabella Ade; Utomo, Kamila Izza; Putri, Novia Ariyana Ramadhani; Azzuhri, Yudhistira Syihab (Varians Statistik Kesehatan, 2025)
Background: Indonesia is transitioning from a curative to a preventive–promotive health paradigm as part of its national health system transformation toward Indonesia Emas 2045. Yet, an aging population, rising chronic disease burden, and geographic inequities threaten to overwhelm hospital capacity and the single-payer JKN system. The Hospital Without Walls (HWW) model—hospital-grade care extended into homes and communities through digital monitoring, telemedicine, and national interoperability—offers a systems-level redesign rather than a technology experiment. Methods: A narrative review was conducted using structured PubMed/MEDLINE searches (2014–2025) targeting core HWW components: hospital-at-home (HaH) with remote patient monitoring (RPM), ward-based continuous monitoring, pre-hospital telemedicine (smart ambulance), home/smart-home sensing, AI-assisted triage, and economic evaluations. Eligible PubMed-indexed RCTs, systematic reviews, and cohort studies were thematically synthesised around safety, efficiency, costs, and implementation relevance to Indonesia. Results: Nine high-quality studies indicate that HaH with RPM achieves non-inferior—and often superior—clinical outcomes and cost efficiency compared with conventional inpatient care. Pre-hospital telemedicine accelerates decision-making for time-critical conditions such as stroke and STEMI, while continuous monitoring and AI triage demand strong alert governance and local validation. Persistent risks of alarm fatigue, data gaps, and digital inequity emphasise the need for structured workflows and equitable design. Conclusion: Implementing HWW in Indonesia requires aligning JKN incentives (HaH iDRG tariffs, shared-savings mechanisms, risk-adjusted capitation), strengthening SATUSEHAT as the national utility layer, and ensuring workforce and connectivity readiness across regions. With these enablers, Indonesia can transform its health system from reactive to proactive—from curative to preventive—achieving safe, equitable, and sustainable distributed care by 2045.